EVALUASI KEBIJAKAN OTONOMI KHUSUS DI DISTRIK KUALA KENCANA KABUPATEN MIMIKA PROVINSI PAPUA : STUDI TENTANG PENINGKATAN KUALITAS SDM - Murib, Demianus (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract : The implementation of special autonomy in Papua province has been going forapproximately 15 years. Along with the various programs and assistance for the construction /development of human resources disbursed by the central government. Regional governments are alsothe special autonomy possessed authority to implement various programs and activities for humanresource development of the people of Papua. But the extent of the special autonomy policy has beenable to provide results and positive impact in improving the quality of human resources in Papua?.The interesting question to be answered and analyzed through a scientific investigation, so the authorsraise the title of the study: "Evaluation of the Special Autonomy Policy in Kuala Kencana MimikaDistrict of Papua Province: Study on Improving the Quality of Human Resources.The method used in this research is descriptive-qualitative method, with the focus of this study is the"result" of the special autonomy in Papua Province can improve the quality of human resources in thecommunity Mimika District of Kuala Kencana. Informants in this study will be taken in three (3) inthe region Kampung Kuala Kencana district Utikini namely Kampung Baru, Kampung Bhintuka, andKampung Karang Glad. Informal comprising elements of the District Government, the GovernmentKampung.tokoh community / cultural / religious, and citizen informants masyarakat.Jumlah as manyas 10 people with the details as follows: Chief of District 1, village head 3, Community Leaders /Religious / Traditional 3, Residents community 3.The results of this study are of special autonomy policy has been to promote development in the field ofeducation so that the educational facilities in the district of Kuala Kencana be available in adequatestarting from elementary, junior high to high school. The availability of educational facilities haveresulted in increased capacity and opportunity to participate in school-age society / obtain an adequatelevel of education so that the educational degrees increases. Special autonomy policy has been topromote development in the health sector so that health facilities in the district of Kuala Kencana beprovided with adequate ie health centers, health centers, mobile health clinics, medical centers, andclinics Public Healt Malaria Control (PHMC). With the availability of facilities / health infrastructurehave resulted in increased public's ability to meet the needs of service / health care so that theincreased level of public health and family nutrition, especially children under five and pregnant andlactating mothers continues to rise.Key word : Evaluation Special Autonomy Policy , Improvement of Human Resources Quality